Medizinbibliothekarische Bibliografie 2019 - Bauer, Bruno (GMS Medizin – Bibliothek – Information, 2020)
The Medical Librarian’s Bibliography 2019 lists all articles from GMS Medizin – Bibliothek – Information and selected publications relevant to medical librarians from following journals: ABI Technik, Bibliothek – Forschung und Praxis, Bibliotheksdienst, B.I.T. online, BuB: Forum Bibliothek und Information, Information – Wissenschaft & Praxis, Journal of EAHIL: European Association for Health Information and Libraries, Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare, o-bib. Das offene Bibliotheksjournal, Zeitschrift für Bibliothekswesen & Bibliographie. The list also includes articles from medical journals written by staff of medical libraries. In such cases, entries of authors were only created if they are working in medical libraries.